Pengaruh Culturally Responsive Teaching Terhadap Partisipasi dan Motivasi Siswa dalam Pembelajaran IPAS Kelas V SDN 060812 Medan - Nawa, Khairun; Sirait, Dahlia; Yarshal, Dinda; Erlinda, Erlinda; Siregar, Nur Salimah (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the effect of culturally responsive teaching on student participation and motivation in Social Science and Natural Science (IPAS) learning in fifth-grade students at SDN 060812 Medan. This study is a Classroom Action Research (CAR) with 20 fifth-grade students as the subjects. The Minimum Completeness Criteria (KKM) for individual students in IPAS is 75, while the KKM for the class is 80%. Data were collected through student activity observation sheets, motivation questionnaires, and test results. Data analysis was performed using percentage techniques. The results of the study show a significant increase in student participation and motivation. In the first cycle, student participation reached 68.50% (good category), while student motivation was 70.25% (good category). In the second cycle, participation increased to 74.00% (good category), and student motivation reached 76.50% (good category). In the third cycle, a more significant improvement was observed, with student participation reaching 85.50% (very good category), and student motivation reaching 88.00% (very good category). Therefore, the implementation of culturally responsive teaching was proven effective in improving student participation and motivation in IPAS learning in fifth grade student at SDN 060812 Medan